The Importance of Respecting Client Values in the Counseling Process - Beni Azwar; Maemunah Maemunah (Suluh: Jurnal Bimbingan dan Konseling, 2025)
This research aimed to analyze the importance of respecting clients' values ​​in the counseling process and its impact on therapy outcomes. The research methodology used a literature study approach and meta-analysis of relevant books and journal articles regarding the role of values ​​in therapy. The articles were selected based on the inclusion criteria of empirical studies, literature reviews, and meta-analyses that addressed the impact of client values ​​in counseling. The results showed that: First; counselors who respect and integrate client values ​​in therapeutic approaches significantly increase client satisfaction and engagement, as well as positive therapeutic outcomes. Second; clients who felt valued showed higher levels of trust and commitment to the counseling process. The findings emphasize the importance of counselor training in religious, cultural, social community and empathy competencies to improve the quality of counseling services. The study recommends the integration of client values ​​as a key element in an effective and holistic counseling approach to achieve better and sustainable outcomes.